Investigating the Relationship between Nutritional Attitude and Performance with Physical Activity in Patients with COVID-19 - Zahra Negarandeh; Hossain Faramarzi; Siavash Babajafari; Mohsen Davoodi; Seyed Ali Hoseini; Omid Reza Salehi; Morteza Zare (Shiraz University of Medical Sciences, 2023)
Background: This study aimed to investigate the relationship between nutritional performance and physical activity in patients with COVID-19.Methods: In this causal-comparative ex-post facto study, after obtaining a license from Shiraz University of Medical Sciences, 600 people who volunteered to participate in the present study were selected as the statistical sample. After completing the demographic information and informed consent forms, subjects completed the Nutritional Knowledge Questionnaire and the International Physical Activity Questionnaire (IPAQ). Onesample t-test, Spearman correlation coefficient, Mann-Whitney U and regression tests were used to analyze the data. The data were analyzed using SPSS software version 22, and a significant level of 0.05 for data analysis was considered.Results: The levels of BMI, nutritional attitude, nutritional knowledge, and nutritional performance of men and women with COVID-19 were unsatisfactory (P≥0.05). Nutritional knowledge scores in women were significantly higher than in men (P≥0.05). With decreasing physical activity, nutritional performance levels increased in women and men; with decreasing nutritional attitudes, physical activity levels increased in men. Also, BMI levels improved with increasing nutritional knowledge scores (P≥0.05).Conclusion: It seems that lack of proper physical activity, attitude, and poor nutritional performance are the factors affecting the increase in the number of COVID-19 patients; therefore, it is recommended that health centers provide the necessary training on the optimal role of physical activity, attitude, and nutritional performance in the prevention of COVID-19 disease.